(untitled) (Journal of Psychiatrists’ Association of Nepal, 2019)
Introduction: Schizophrenia is a clinical syndrome of variable, but profoundly disruptive psychopathology. Though it is one of the top ten illness contributing to global burden of disease, relapse rate in schizophrenia is high. Globally relapse rate varies from 50% to 92% and are similar in developed and developing countries. There are various factors associated with relapse, common being poor adherence to treatment. The estimated rate of non-adherence in schizophrenia are 50% widely ranging from 4% to 72%. This study was aimed to find the socio-demographic status of non-adherent group, contributing factors and their severity. Material and Method: A descriptive, cross-sectional study among 95 schizophrenia relapsed patients seeking psychiatric inpatient services at Nepal Medical College Teaching Hospital, Attarkhel, Nepal from the period of Baisakh 3rd 2074 to Baisakh 4th 2075. The socio-demographic variables and clinical data of patients were recorded on proforma developed by department of Psychiatry. The severity of illness was assessed by using The Brief Psychiatric Rating Scale (BPRS) and Positive And Negative Syndrome Scale (PANSS). Also, medication adherence was assessed using Medication Adherence Rating Scale (MARS). Results: Out of 95 relapsed patients, greater number (62.1%) were non-adherent to medication and (37.9%) were adherent to medication. Also, the symptom severity assessment showed significantly severe relapse in non-adherent patient group (43.1%) than adherent patient group (3.1%). Conclusion: Non-adherent to medication is associated with significantly severe relapse in patients of Schizophrenia. Therefore, improving adherence to medication can be achieved by focusing on the identified multitude of factors driving non-adherence.